2016
DOI: 10.1021/acs.est.5b04834
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Manganese Phase Dynamics during Biological and Abiotic Manganese Oxide Reduction

Abstract: Manganese oxides are often highly reactive and easily reduced, both abiotically, by a variety of inorganic chemical species, and biologically during anaerobic respiration by microbes. To evaluate the reaction mechanisms of these different reduction routes and their potential lasting products, we measured the sequence progression of microbial manganese(IV) oxide reduction mediated by chemical species (sulfide and ferrous iron) and the common metal-reducing microbe Shewanella oneidensis MR-1 under several endmem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 75 publications
3
33
0
Order By: Relevance
“…1). Steady-state was thus reached in less than 1 d of contact time, consistent with previous observations showing that feitknechtite is formed in less than 20 min (Johnson et al, 2016) and that sorption of Mn 2þ at the d-MnO 2 surface is completed within less than 1 s (Fendorf et al, 1993).…”
Section: Mineralogical Evolutionsupporting
confidence: 90%
“…1). Steady-state was thus reached in less than 1 d of contact time, consistent with previous observations showing that feitknechtite is formed in less than 20 min (Johnson et al, 2016) and that sorption of Mn 2þ at the d-MnO 2 surface is completed within less than 1 s (Fendorf et al, 1993).…”
Section: Mineralogical Evolutionsupporting
confidence: 90%
“…Indeed, Postma and Appelo (63) showed that reduction of manganite by sulfide and ferrous iron could reach completion within 10 h under ambient conditions. Johnson et al (64) showed rapid reduction of MnO x by sulfide and ferrous iron also within 10 h. In addition, microorganisms can also facilitate reduction of MnO x using organic matter. This is a major process of the Mn cycle in modern seawater.…”
Section: Discussionmentioning
confidence: 99%
“…In soil, P generally is chemically bound within minerals (e.g., apatite) and organic substances (e.g., phospholipids), is sorbed to the minerals or organic surfaces predominantly as phosphate ion and occurs in the equilibrium soil solution as H 2 PO 4 − or HPO 4 2− . Under oxic conditions, phosphate ions might be sorbed to binding sites of clay minerals and/or Al, Fe and Mn (hydr)oxides with which they can form insoluble complexes (Lijklema 1980 ; Penn et al 2005 ; Johnson et al 2016 ). However, if controlled drains are closed, increased water content may lead to reducing conditions in soil.…”
Section: Introductionmentioning
confidence: 99%